New technology for measuring the in situ performance of rock bolts - Hyett, A.; Spearing, Sam (2012)
Understanding the interaction between rock bolts and underground rock movement is critical for safe and cost effective underground excavation design. Although early research on this subject involved a balance of theoretical analysis and field measurement, recent work has been heavily focused on analytical and numerical studies. This paper describes technology that has the potential to redress the balance through instrumentation of rock bolts deployed under routine operating conditions in underground mines Almost all previous instrumented rock bolt studies have used core technologies based on resistive strain gauges according to two scenarios (i) load cells positioned at the head of the bolt, and (ii) resistance strain gauge arrays recessed into grooves along the length of the bolt. Both approaches are complimentary with the selection criterion for each depending on factors such as whether the rock-bolt is fully grouted or end-anchored. A new product is introduced in this paper. The d-REBAR involves an array of small-diameter long-base-length displacement sensors recessed into grooves along the entire length of the bolt. The transducers are interfaced with on-board digital signal conditioning and telemetry. Methodologies for the deployment of the new instrumentation are presented, and guidelines are presented for the interpretation of results obtained based on data obtained from field trials. The results demonstrate the viability of these new technologies and moreover provide important insight into rock bolt/rock mass interaction. Copyright 2012 ARMA, American Rock Mechanics Association.